Strongyloides stercoralis hyperinfection: a dreaded but still missed diagnosis - Milton Roberto Furst Crenitte; Fernando Peixoto Ferraz de Campos; Aloísio Felipe-Silva (University of São Paulo, 2012)
Strongyloides stercoralis (S. stercoralis), an intestinal nematode, is endemic in tropical and subtropical regions, being less prevalent in temperate climates. The number of infected persons worldwide ranges between 10 million and 100 million people. In Brazil the reported prevalence is 13%. Chronic infection may be asymptomatic or accompanied by gastrointestinal and respiratory symptoms. Under immunosuppressive conditions, the infection assumes serious proportions frequently accompanied by septic shock, disseminated intravascular coagulopathy and respiratory distress syndrome. The authors report a case of a 50-year-old female patient who was a chronic user of glucocorticoids and had been seeking medical attention for two months because of continuous gastrointestinal symptoms. She was admitted to the emergency room with clinical signs of septic shock and died after four days despite an adequate antibiotic regimen, vasopressor drugs, and ventilatory support. The autopsy revealed the unsuspected finding of  S. stercoralishyperinfection and septicemia.